2011
DOI: 10.1007/s00192-011-1543-8
|View full text |Cite
|
Sign up to set email alerts
|

Twelve months effect on voiding function of retropubic compared with outside-in and inside-out transobturator midurethral slings

Abstract: There was no difference for Qmax at 12 months between TVT, TOT and TVT-O. Female sexual dysfunction and tape exposure may be higher with a transobturator tape.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 30 publications
0
37
0
2
Order By: Relevance
“…However, in another study comparing retropubic, transobturator outside-in, and inside-out tension-free vaginal tape procedures, the outside-in transobturator sling had an increased de novo rate of female sexual dysfunction than the retropubic or inside-out transobturator ones at 12 months [40].…”
Section: Overactive Bladder Symptoms and Sexual Function After Musmentioning
confidence: 92%
“…However, in another study comparing retropubic, transobturator outside-in, and inside-out tension-free vaginal tape procedures, the outside-in transobturator sling had an increased de novo rate of female sexual dysfunction than the retropubic or inside-out transobturator ones at 12 months [40].…”
Section: Overactive Bladder Symptoms and Sexual Function After Musmentioning
confidence: 92%
“…9,110,143 In studies of effectiveness and safety, pain was mostly divided into perioperative pain and pain lasting more than 6 weeks. Perioperative pain has been reported in up to 33% of patients, 252 occurring more frequently after implantation of TOT slings than RP slings, 331 and chronic pain (of any definition) has been reported in 0-31% of patients (REFS 17,18,20,30,39,47,48,53,58,59,(61)(62)(63)66,69,70,73,76,79,82,(89)(90)(91)95,98,99,140,152,155,159,164,167,168,(171)(172)(173)(174)177,(180)(181)(182)185,208,…”
Section: Reviewsmentioning
confidence: 98%
“…Compression from the sling is by far the most common cause of urethral obstruction, and at least one case of urethral stricture accompanied by urethral erosion has been reported. 9 The incidence of urethral obstruction requiring surgical intervention ranges from 0% to 8.9% in patients fitted with RP slings and from 0% to 21.3% for those with TOT slings (REFS 17,18,20,21,23,26,30,(46)(47)(48)(50)(51)(52)(53)(54)(55)(56)58,59,(61)(62)(63)(64)(66)(67)(68)(69)71,74,77,(80)(81)(82)(83)(86)(87)(88)(89)(90)(91)(92)(97)(98)(99)148,159,163,166,…”
Section: Oab Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…26,27,30,[32][33][34][35]37,[40][41][42]46,47 In the other studies, TVT and Monarc (American Medical Systems, Minnetonka, MN, USA) were compared. 28,31,40,44 One study, . 29 Of the studies found in this comparison group, only one 31 did not present results for objective cure.…”
Section: Retropubic Sling Versus Transobturator Slingmentioning
confidence: 99%